Hylaperdina squamosa, a new species of Neotropical Lycoperdininae (Coleoptera, Endomychidae) from Brazil - Arriaga-Varela, Emmanuel; Tomaszewska, Wioletta (Zootaxa, 2016)
Endomychidae or Handsome Fungus Beetles are a moderately large family of mycophagous beetles distributed worldwide but with the highest diversity in the tropics (Shockley et al. 2009a, b). The concept of the family (e.g. Lawrence & Newton 1995; Tomaszewska 2000, 2010; Shockley et al. 2009a) has recently been restricted by an elevation of former subfamilies Eupsilobiinae, Mycetaeinae and Anamorphinae to the level of independent families in the newly recognized superfamily Coccinelloidea (Robertson et al. 2015).